Divine images and human imaginations in Ancient Greece and Rome - Mylonopoulos, Jannis (Leiden Boston Brill, 2010)
Preliminary material /Joannis Mylonopoulos -- Introduction: DIVINE IMAGES VERSUS CULT IMAGES. AN ENDLESS STORY ABOUT THEORIES, METHODS, AND TERMINOLOGIES /Joannis Mylonopoulos -- A PANTHEON WITHOUT ATTRIBUTES? GODDESSES AND GODS IN MINOAN AND MYCENAEAN ICONOGRAPHY /Fritz Blakolmer -- ANICONISM AND THE NOTION OF THE “PRIMITIVE” IN GREEK ANTIQUITY /Milette Gaifman -- FINDING THE GODS GREEK AND CYPRIOT VOTIVE KORAI REVISITED /Catherine M. Keesling -- GODS AND STATUES—AN APPROACH TO ARCHAISTIC IMAGES IN THE FIFTH CENTURY BCE /Fernande Hölscher -- GREEK PRIESTS AND “CULT STATUES”: IN HOW FAR ARE THEY UNNECESSARY? /Vinciane Pirenne-Delforge -- THESEUS AND THE STONE THE ICONOGRAPHIC AND RITUAL CONTEXTS OF A GREEK VOTIVE RELIEF IN THE LOUVRE /Gunnel Ekroth -- ODYSSEUS WITH A TRIDENT? THE USE OF ATTRIBUTES IN ANCIENT GREEK IMAGERY /Joannis Mylonopoulos -- THE LIFE STORY OF A CULT STATUE AS AN ALLEGORY: KALLIMACHOS’ HERMES PERPHERAIOS /Ivana Petrovic -- ARCADIAN CULT IMAGES BETWEEN RELIGION AND POLITICS /Tanja S. Scheer -- SYNNAOS THEOS IMAGES OF ROMAN EMPERORS IN GREEK TEMPLES /Dirk Steuernagel -- SIMULACRA DEORUM VERSUS ORNAMENTA AEDIUM THE STATUS OF DIVINE IMAGES IN THE TEMPLES OF ROME /Sylvia Estienne -- THE DEDICATION OF CULT STATUES AT THE ALTAR. A ROMAN PICTORIAL FORMULA FOR THE INTRODUCTION OF NEW CULTS /Katja Moede -- ORNAMENTA, MONUMENTA, EXEMPLA GREEK IMAGES OF GODS IN THE PUBLIC SPACES OF CONSTANTINOPLE /Alessandra Bravi -- BIBLIOGRAPHY /Joannis Mylonopoulos -- INDEX OF PASSAGES CITED /Joannis Mylonopoulos -- SUBJECT INDEX /Joannis Mylonopoulos -- FIGURES /Joannis Mylonopoulos.
The polytheistic religious systems of ancient Greece and Rome reveal an imaginative attitude towards the construction of the divine. One of the most important instruments in this process was certainly the visualisation. Images of the gods transformed the divine world into a visually experienceable entity, comprehensible even without a theoretical or theological superstructure. For the illiterates, images were together with oral traditions and rituals the only possibility to approach the idea of the divine; for the intellectuals, images of the gods could be allegorically transcended symbols to reflect upon. Based on the art historical and textual evidence, this volume offers a fresh view on the historical, literary, and artistic significance of divine images as powerful visual media of religious and intellectual communication
Paperback version published 2015
Includes bibliographical references (p. 303-359) and indexes
Keywords: Idols and images -- Greece; Idols and images -- Rome; Idols and images; Religion; Greece -- Religion; Rome -- Religion; Greece; Rome (Empire); Aufsatzsammlung; Konferenzschrift -- 2007 -- Erfurt; Konferenzschrift